HUBUNGAN ANTARA KEPERCAYAAN DIRI DAN KECEMASAN TERHADAP KETERAMPILAN BERBICARA BAHASA INGGRIS - Uput, Pramesti Nurita Putri; Purwani, Retno; Winarni, Lastri Mei (Nusantara Hasana Berdikari, 2022)
Based on preliminary study conducted at the Faculty of Health Sciences Muhammadiyah University of Tangerang, out of 10 people interviewed, 60% had low anxiety, 80% less confidence, and 70% less English speaking style. Research objectives : To find out whether there is a link between confidence and anxiety to the ability toÂ English speaking syle in students of the Faculty of Health Sciences, University of Muhammadiyah Tangerang. Research methods : The type of research used is descriptive type of quantitative research. Sampling techniques using Total Sampling techniques with a total of 102 students / I at the Faculty of Health Sciences, University of Muhammadiyah Tangerang, data collection using questionnaires. Data analysis using frequency distribution or Univariate, Bivariate and Cross Sectional approaches. Results of the study : Based on the results of the Chi-Square test that p-value = 0.000 < 0.05, it is stated that Ha is accepted, meaning there is a relationship between confidence and anxiety about the ability to English speaking style in students of the Faculty of Health Sciences, Muhammadiyah University of Tangerang.Â Conclusions and suggestions : There is a link between confidence and anxiety about english speaking style in students of the Faculty of Health Sciences, University of Muhammadiyah Tangerang. It is recommended for students to be able to make efforts to improve the quality of English by practicing english vocabulary a lot.